High-dose intravenous methylprednisolone in rheumatoid arthritis. Issue 5 (October 1982) - Forster, P J; Grindulis, K A; Neumann, V; Hubball, S; McConkey, B
Abstract : Fourteen patients with severe rheumatoid arthritis (RA) were given 27 courses of methylprednisolone intravenously, each of 3 infusions of 1 g on alternate days. After 7 days there was marked improvement in clinical state and most laboratory tests; levels of ESR and 4 serum acute-phase proteins, C3, C, IgG, and IgA, fell significantly. Serum IgM and rheumatoid factor titre were unchanged. 125I C1q binding fell in all instances where it was initially raised. Clinical remission lasted a mean of 10 weeks. Serum C-reactive protein (CRP) fell to less than 30 mg/l after all courses except one within 7 days and rose above this figure after a mean of 7 weeks. The ESR fell below 30 mm/h within seven days in 17 courses and remained below this value for a mean of 7 weeks. Three patients had clinical remissions, with serum CRP less than 30 mg/l and ESR less than 30 mm/h, lasting more than 42 weeks.